Long Chain Non Coding RNA Targeting miR Signal Axis Regulates the Mechanism of Apoptosis and Invasion and Migration of Glioma U251 Cells - Zhao, Hailin; Li, Shiwei; Wang, Lulu; Luo, Dongdong; Hu, Su; Li, Dan; Peng, Biao (Cellular and Molecular Biology, 2022)
The occurrence of glioma is gradually promoted by various factors, and it has gone through multiple stages of development, involving abnormal expression of multiple genes. One of the important reasons for the development of gliomas is the interaction of genetic factors and the environment. Non-coding transcripts can also form this high-level structure, and the formation of binding sites for interactions between lncRNA and proteins, DNA, and other RNA molecules may be related to their structural diversity. Due to the importance of glioma-related research and the potential effectiveness of lncRNA, this paper focuses on the mechanism of long-chain non-coding RNA targeting the Mir signal axis to regulate apoptosis, invasion and migration of glioma U251 cells. In this paper, human glioma cell line U251 was used as experimental material for simulation analysis. The results showed that after miR simulation, the pass rate of U251 stem cells through the filter was 17.3%, which was significantly less than 85.4% of group C; compared with 77.6% of the negative control group, the cell penetration rate of the miR inhibitor group was significantly improved. 92.5%. The miR expression level can affect the invasion ability of U251 stem cells, and can negatively regulate the expression of fzd4 to inhibit the invasion and metastasis of glioma U251 cells.